2020
DOI: 10.2478/sgem-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of mechanical properties on the example of aggregates of Carpathian sandstones

Abstract: The constantly growing, broadly understood, construction industry requires the use of a large amount of aggregates. The construction of roads, motorways, railway lines and hydrotechnical structures requires the use of aggregates of high quality, which is primarily determined by mechanical properties. The basic parameters describing mechanical properties of aggregates are the Los Angeles (LA) fragmentation resistance coefficient and the Micro-Deval (MDE) abrasion resistance coefficient. The LA and MDE coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A similar impact of penetration curve adjustments on CBR results was found for mixtures with the grading of 0-63 mm (Figs. [16][17][18][19]. The adjustment of the concave portion of the curve resulted in an increase in CBR.…”
Section: Test Resultsmentioning
confidence: 99%
“…A similar impact of penetration curve adjustments on CBR results was found for mixtures with the grading of 0-63 mm (Figs. [16][17][18][19]. The adjustment of the concave portion of the curve resulted in an increase in CBR.…”
Section: Test Resultsmentioning
confidence: 99%
“…research into aggregate wear and fragmentation resistance tests address issues of mutual relationships and correlations between aggregate properties [3,11,14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Analysis and Modifications Of Test Methodsmentioning
confidence: 99%
“…The review results also suggest that the mineral composition, structure, and size of mineral components definitely have a significant influence on the resistance to wear and fragmentation. Interestingly, the majority of publications related to research into aggregate wear and fragmentation resistance tests address issues of mutual relationships and correlations between aggregate properties [ 3 , 11 , 14 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Wear and Fragmentation Resistance Of Mineral Aggregates—a Review Of Micro-deval And Los Angeles Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that if we have one of these values determined by the test, it is possible to estimate another two related values based on the known correlations. The next example is article [53], in which dependence between the mechanical and geometric properties of aggregates was verified, i.e., aggregate (arches and mixtures) produced from sands of layers of Magura or Cergo. An analysis was carried out for dependence between the Los Angeles index, Micro-Deval index, and flatness and shape indicators.…”
Section: Literature Reviewmentioning
confidence: 99%